Reducing the Cognitive Footprint of Brain Tumor Surgery - Dadario, Nicholas B.; Brahimaj, Bledi; Yeung, Jacky; Sughrue, Michael E. (Frontiers in Neurology, 2021)
The surgical management of brain tumors is based on the principle that the extent of resection improves patient outcomes. Traditionally, neurosurgeons have considered that lesions in “non-eloquent” cerebrum can be more aggressively surgically managed compared to lesions in “eloquent” regions with more known functional relevance. Furthermore, advancements in multimodal imaging technologies have improved our ability to extend the rate of resection while minimizing the risk of inducing many new neurologic deficits, together referred as the “onco-functional” balance. However, despite the common utilization of invasive techniques such as cortical mapping to identify eloquent tissue responsible for language and motor functions, glioma patients continue to present post-operatively with poor cognitive morbidity in higher-order functions. Such observations are likely related to the difficulty in interpreting the highly-dimensional information these technologies present to us regarding cognition in addition to our classically poor understanding of the functional and structural anatomy underlying complex higher-order cognitive functions. Furthermore, reduction of the brain into isolated cortical areas without consideration of the complex, interacting brain networks which these regions function within to subserve higher-order cognition inherently prevents our successful navigation of true eloquent and non-eloquent cerebrum. Fortunately, recent large-scale movements in the neuroscience community, such as the Human Connectome Project, have provided updated neural data detailing the many complex macroscopic connections between cortical regions which integrate and process the information underlying complex human behavior within a brain “connectome”. Connectomic data can provide us better maps on how to understand human cortical and subcortical relationships between tumor and human cerebrum such that neurosurgeons can begin to make more informed decisions during surgery to maximize the onco-functional balance. However, connectome-based neurosurgery and neurorehabilitation is relatively nascent and requires further work moving forward to optimize our ability to add highly valuable connectomic data to our surgical armamentarium. In this manuscript, we review four concepts with detailed examples which will likely help us better understand cognitive outcomes and provide a guide for how to utilize connectomics to reduce cognitive morbidity following cerebral surgery.